Seismic Performance of Tuned Liquid Column Dampers for Structural Control Using Real-Time Hybrid Simulation. Issue 8 (16th November 2016) - Zhu, Fei; Wang, Jin-Ting; Jin, Feng; Lu, Li-Qiao
Abstract : This article presents real-time hybrid simulation (RTHS) in a single-degree-of-freedom (SDOF) steel frame incorporated with tuned liquid column damper (TLCD). The SDOF steel frame is numerically simulated, and the TLCD alone is physically experimented on a shaking table. The delay-dependent stability of RTHS system for TLCD investigation is first assessed; and the delay-dependent accuracy is verified by comparing the responses obtained through the RTHS, the conventional shaking table test, and an analytical solution. Then, RTHSs are carried out to evaluate the effects of mass ratio, structural damping ratio, structural stiffness, and peak ground acceleration on the reduction effectiveness of STLCD. The nonlinear behavior of the STLCD is experimentally captured. Finally, the structural responses under STLCD and multiple TLCDs (MTLCD) control are compared. It is found that the performance of STLCD strongly depends on structural parameters and properties of earthquakes; both MTLCD and STLCD induce approximately the same response reductions, and the former can enhance the control performance in certain cases. These results presented here may contribute to improve the design and application of TLCDs in practical engineering.